2015
DOI: 10.1126/science.aaa5111
|View full text |Cite
|
Sign up to set email alerts
|

Reversible centriole depletion with an inhibitor of Polo-like kinase 4

Abstract: Centrioles are ancient organelles that build centrosomes, the major microtubule-organizing centers of animal cells. Extra centrosomes are a common feature of cancer cells. To investigate the importance of centrosomes in the proliferation of normal and cancer cells, we developed centrinone, a reversible inhibitor of Polo-like kinase 4 (Plk4), a serine-threonine protein kinase that initiates centriole assembly. Centrinone treatment caused centrosome depletion in human and other vertebrate cells. Centrosome loss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

67
581
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 404 publications
(653 citation statements)
references
References 60 publications
67
581
5
Order By: Relevance
“…Therefore, we aimed to uncouple increased ploidy from increased centrosome numbers, two main events occurring concomitantly with cytokinesis failure (Holland and Cleveland 2009). To this end, we used centrinone, a Polo-like-kinase 4 (PLK4) inhibitor, leading to centriole depletion by blocking their duplication during S phase (Wong et al 2015). A 24-h cotreatment of A549 or U2OS cells with an agent triggering cytokinesis failure plus centrinone led to a measurable loss of centrioles without impinging on centrosome abundance (note that the two centrosomes per cell failing cytokinesis comprise either two centrioles each or only one centriole, depending on the presence or absence of centrinone, as opposed to one centrosome for each control cell) ( Fig.…”
Section: The Piddosome Limits Polyploidization During Liver Organogenmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, we aimed to uncouple increased ploidy from increased centrosome numbers, two main events occurring concomitantly with cytokinesis failure (Holland and Cleveland 2009). To this end, we used centrinone, a Polo-like-kinase 4 (PLK4) inhibitor, leading to centriole depletion by blocking their duplication during S phase (Wong et al 2015). A 24-h cotreatment of A549 or U2OS cells with an agent triggering cytokinesis failure plus centrinone led to a measurable loss of centrioles without impinging on centrosome abundance (note that the two centrosomes per cell failing cytokinesis comprise either two centrioles each or only one centriole, depending on the presence or absence of centrinone, as opposed to one centrosome for each control cell) ( Fig.…”
Section: The Piddosome Limits Polyploidization During Liver Organogenmentioning
confidence: 99%
“…The following drugs were used alone or in combination: 0.5 µM reversine (Enzo Life Sciences, BML-SC104), 100 nM nocodazole (Sigma-Aldrich, M1404), 100 nM taxol (Sigma-Aldrich, T7191), 100 ng/mL doxorubicin (Sigma-Aldrich, D1515), 2 μM ZM447439 (Selleck Chemicals, S1103), 4 μM DHCB (Sigma-Aldrich, D1641), 125 nM centrinone (Wong et al 2015), 2 mM thymidine (Sigma-Aldrich, T1895), 1 μg/mL doxocycline (SigmaAldrich, D9891), and 5 μM nutlin-3 (Sigma-Aldrich, N6287).…”
Section: Drug Treatments and Synchronization Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell cycle defects in Cp110 −/− MEFs Impairment in centrosome biogenesis leads to defects at cell cycle checkpoints, which prevent cells with damaged DNA from replication (G1/S checkpoint) or entering mitosis (G2/M checkpoint) (Lambrus et al, 2015;Wong et al, 2015). The reported role of CP110 in centrosome duplication (Chen et al, 2002) led us to hypothesize a cell cycle progression defect during DNA replication and chromosome segregation at anaphase in Cp110 −/− MEFs.…”
Section: Abnormal Distribution Of Rab11mentioning
confidence: 99%
“…In contrast, human cells can assemble a mitotic spindle even in the absence of centrosomes because of centrosome-independent MT formation and the presence of spindle assembly pathways. Recent studies have shown that the ability of human cells to tolerate loss of centrosomes or centrosome overduplication is reliant upon the inactivation of the p53 tumor suppressor gene that otherwise arrests these abnormal cells in G 1 phase (6,7). How cells sense centrosome number defects is currently not understood.…”
mentioning
confidence: 99%